The rise of artificial intelligence: A savior or saboteur / Syezreen Dalina Rusdi and Nur Zania Azurin Abdullah Sani - Rusdi, Syezreen Dalina; Abdullah Sani, Nur Zania Azurin (Office of the Deputy Vice-Chancellor (Research & Innovation), 2023)
The rapid progress in artificial intelligence (AI) has paved the way for a future full of unprecedented possibilities and opportunities. With its potential to revolutionize industries, reshape businesses, and significantly enhance our everyday experiences, AI is already making its mark on our daily lives. It has taken the lead in boosting emerging technologies such as big data, robotics, and the Internet of Things (IoT). One notable impact of AI's influence is evident in the growing prevalence of virtual assistants like Amazon's Alexa and Apple's Siri, which are increasingly finding their way into homes and workplaces (Housen, 2023). The role of AI as a technological innovator remains dominant, illustrated by the rise of generative AI tools like ChatGPT, AI art generators, and Interior.ai that have gained widespread recognition. Looking ahead, the presence of AI is likely to only increase in the future. One area where AI has already made significant strides is in automation. Machines equipped with AI capabilities can perform repetitive tasks faster, more accurately, and tirelessly, eliminating the need for humans to engage in dull and labor-intensive activities. This allows human resources to focus on more creative and complex endeavors and unleash their full potential. In addition to automation, AI offers intelligent decision-making, data analysis and predictive capabilities that can greatly improve efficiency, safety, and sustainability on a large scale (Akhter et al., 2021). For businesses, the consideration of AI has progressed well beyond the initial question of whether to adopt AI or not. The primary concern now revolves around the effective generation of business value from AI technology.